2018
DOI: 10.1159/000488050
|View full text |Cite
|
Sign up to set email alerts
|

Increased Group 2 Innate Lymphoid Cells Are Correlated with Eosinophilic Granulocytes in Patients with Allergic Airway Inflammation

Abstract: The T helper 2 (Th2)-type response was considered the hypostasis of allergic airway diseases, including asthma and allergic rhinitis (AR). However, more recent studies have suggested that allergic airway inflammation also depends on innate immunity and is closely related to group 2 innate lymphoid cells (ILC2s). This study evaluated the ILC2 levels of asthma subjects, patients with asthma and AR, and healthy individuals, regarding how to investigate the relationship between clinical data and ILC2 levels. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…6,37 Importantly, we reported that peripheral ILC2 levels in patients with AR correlated positively with the severity of the clinical VAS score, and stimulation with epithelium-derived cytokines or specific antigen induced significantly greater production of T H 2 cytokines in PBMCs isolated from patients with AR 6 or those with asthma and AR. 9,13 However, previous studies mostly used flow cytometry to identify ILC2s in the blood, sputum, or sometimes in the tissues. Until now, only 2 groups have provided an in situ characterization of ILC2s in the skin of the patients with systemic sclerosis 38 and atopic dermatitis and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,37 Importantly, we reported that peripheral ILC2 levels in patients with AR correlated positively with the severity of the clinical VAS score, and stimulation with epithelium-derived cytokines or specific antigen induced significantly greater production of T H 2 cytokines in PBMCs isolated from patients with AR 6 or those with asthma and AR. 9,13 However, previous studies mostly used flow cytometry to identify ILC2s in the blood, sputum, or sometimes in the tissues. Until now, only 2 groups have provided an in situ characterization of ILC2s in the skin of the patients with systemic sclerosis 38 and atopic dermatitis and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] We previously reported that there were high levels of ILC2s in the blood of patients with AR and asthma. 6,9,13 Because the biology of the T H cell and the ILC2 subset is greatly shared, there is an analogy between adaptive T cells and their innate lymphoid cell counterparts. 14,15 ILC2s, for example, express high levels of GATA3, which also guides the differentiation of T H 2 cells.…”
mentioning
confidence: 99%
“…54 However, reports since have demonstrated increased activation status and numbers of ILC2s in samples from pediatric and adult asthmatics compared with controls. 3,18,5557 One report found increased peripheral blood ILC2s and Th2 cytokine levels in allergic asthmatics compared with healthy controls and patients with allergic rhinitis. 18 The first study to assess airway ILC2s showed that cytokine producing ILC2s are increased in the sputum of severe asthmatics compared with mild asthmatics and healthy controls.…”
Section: Ilc2s In Human Allergic Airway Diseasementioning
confidence: 99%
“…Another report, and in parallel with nasal polyp ILC2 studies, found that numbers of ILC2s in asthmatics correlated with numbers of eosinophils. 57 Interestingly, a recent human and mouse ILC2 transcriptomic and epigenomic study showed that ILC2 programs are specifically linked with known asthma susceptibility genes (including rora, smad3, gata3, il13, il18r1, and il1rl1) suggesting ILC2s may be key effectors in part regulated by genetic susceptibility in asthma. 61 Overall, most studies suggest an increase of activated ILC2s in samples from asthma subjects and detailed animal studies (reviewed elsewhere 12 ) support a role for ILC2s in airway hyperresponsiveness, lung eosinophilia, and mucus production.…”
Section: Ilc2s In Human Allergic Airway Diseasementioning
confidence: 99%
“…1 Repeated hospitalizations with infectious disease increase the risk of hospital-acquired infection and increase the socioeconomic burden. 2,3 Immunoglobulin E (IgE) is produced by plasma cells in the lamina propria of the nasopharynx, tonsils, bronchus, and gastrointestinal mucosa and mediates type I allergy, 4 such as bronchial asthma 4,5 and rhinitis, 6,7 and is associated with the prevalence of lower airway infections. 8 Children with asthma and chronic sinusitis have a significantly increased risk of bronchopneumonia and pneumonia, 9,10 suggesting that IgE levels may be associated with the occurrence of bronchopneumonia.…”
Section: Introductionmentioning
confidence: 99%